Are schools in Malaysia ready to open? - Norhayati Mohd Zain; Nur Anis Izzati Che Mut; Medina Marzukhi; Siti Hajar Norhan (International Journal of Evaluation and Research in Education (IJERE), 2022)
The decision on school reopening has evoked mixed reactions from parents as they become nervous regarding this action and are uncertain to send their children to school. Therefore, this study was conducted to assess the teachers’ perspectives on the readiness and challenges of school reopening in Malaysia. A study was conducted through online interview sessions amongst 20 teachers for primary and secondary schools at Seremban district, Negeri Sembilan, Malaysia from October 2020 until February 2021. Data were coded into themes and sub-themes based on the similarities of the data. The respondents in this study agreed that they are ready for school reopening and fully follow the guidelines prepared by the Ministry of Education Malaysia such as checking body temperature, physical distancing inside and outside the classroom, enforcement of wearing mask and sanitize the area regularly. Undeniably, the teachers faced some challenges regarding new norms during school sessions. Therefore, to ensure that the students receive proper education, at the same time the measures to contain the transmission of COVID-19 are followed properly, a few suggestions have been made. The cooperation from the teachers, parents and students are also needed to ensure and achieve the smoothness of school sessions.